The effect of increasing running speed on three-dimensional changes of lower limb joint angles in open motor chain and swing phase - Mohammad Soltani; Ali Fatahi; Razieh Yousefian Molla (Biyumikānīk-i varzishī)
Objective Running is known as one of the most popular sports for which there is no time and space limit. Recently, due to lifestyle changes, the use of treadmills for walking and running has increased. However, the biomechanical differences in coordination between running on a treadmill at different speeds have not been sufficiently addressed. The aim of this study was to investigate the effect of increasing running speed on three-dimensional changes of lower extremity joint angles in the open motor chain and swing phase. Methods 28 elite runners participated in this study. Subjects ran on an equipped treadmill while kinematic running data was recorded for 30 seconds through a three-dimensional 12-camera motion recording system at speeds of 2.5, 3.5 and 4.5 m / s. Data were normalized based on the subjects' body mass as well as 101 time points in the running cycle. The normality and homogeneity of variance of the dependent variable were tested using Bartlett and Leven’s tests. Repeated measurement test was performed to measure the angles of the pelvis, knee and ankle between the dominant and non-dominant lower limb joints in the running swing phase. Results In the range of motion of hip, knee and ankle joint, there were significant differences among all the three speed rates of 2.5, 3.5 and 4.5 on all planes. Conclusion Changes in the angle and range of motion of the hip, knee and ankle joints are significantly greater in the swing phase as the running speed increases. Due to the fact that in high-speed running, the stability of the body decreases, the central nervous system commands to increase the range of motion of the angle of the mentioned joints to regulate the structure of the body and reduce the instability in response to the applied disorders. The results also show that the ankle joint, as the closest joint in contact with the ground, helps to run faster and more efficiently by increasing changes in the angle and range of motion of the ankle joint during running, and by reducing the time of foot contact with the ground at each step. It can be concluded that this point is effective in increasing speed.